Comparison of Physical Characteristics and Initial Spoilage of Broiler Chicken Meat from Conventional and Modern Markets in Rogojampi, Banyuwangi Regency - Prima Ayu Wibawati; Lutfiyah Zain; Mufidah Khairunnisa Salsabilla; Salsabila Nurina Naqsmagita; Bernadetha Melarosa Dwi Asmi; Renata Nadia Desideria; Sabrina Nurrahmani (Journal of Basic Medical Veterinary, 2026)
This study aimed to evaluate changes in the physicochemical quality of broiler chicken meat and indicators of incipient spoilage, as determined by the Eber test, obtained from conventional and modern markets in Rogojampi District, Banyuwangi. A total of sixteen samples from each market type were analyzed on days 0, 1, and 2 during chilled storage at approximately 4°C. The assessed parameters included aroma, color, texture, pH, and reactions associated with volatile basic compounds. Data with a normal distribution were analyzed using analysis of variance (ANOVA), followed by Tukey’s or Duncan’s test, while nonparametric data were evaluated using the Kruskal–Wallis test followed by Dunn’s test. The results showed that chicken meat from conventional markets exhibited significant quality degradation in aroma, color, texture, pH, and Eber test responses during storage (p < 0.05). Declines in aroma and color were observed from the initial day, texture degradation became apparent after one day of storage, pH values increased progressively, and positive Eber reactions indicating incipient spoilage were detected on day 2. In contrast, meat from modern markets exhibited significant changes only in aroma and color on day 2 (p < 0.05), while texture remained relatively stable (p > 0.05). Although pH values varied significantly during storage (p < 0.05), no significant spoilage-related reactions were indicated by the Eber test (p > 0.05). These findings indicate that differences in handling and storage practices accelerate quality deterioration in chicken meat from conventional markets. This study was limited to physical parameters and early spoilage indicators without direct microbiological analysis. Improved temperature control and hygiene practices in conventional markets are recommended, and future studies should include microbial profiling and cold-chain monitoring to more comprehensively assess meat safety and spoilage mechanisms.